ROLE OF PRAGMATIC STRATEGIES ON UNIVERSITY CAMPAIGN - Yunika Triana; Nugroho, Arif (Center of Language and Cultural Studies [CLCS], 2022)
This paper aims to provide information that pragmatic strategies is needed to offer university campaign. It is related to applied linguistics that make brand of universities known by many people. There are theory namely Ethos, Pathos and Logos that need to implement advertiser to make attention and awareness of the target audience. The results of this research can also help stakeholders determine the promotion and branding strategy of the institution such as higher education. A great university may not be known to many people, or it may only be known by certain people. Small universities could be even worse. This research is a marketing trial using google ads to increase the number of new student registrants at a State Islamic University (UIN Raden Mas Said Surakarta). Promotion technique is adopted the Aristotle’s rhetoric namely trend consideration (Ethos), fundamental consideration (Pathos) and technical consideration (logos). All of these techniques use a pragmatic strategy approach where the advertiser does not invite the target audience directly, but the university and the target audience are brought together based on core of supply and demand. If compared to the previous year, there will be a 41% increase in registrants in 2021. This strategy has a significant impact and is very influential. A metadata analysis was chosen because this research studied deeply three sources of statistical data including keywords trends, enrolment statistics and a campaign statistic.